(untitled) (Research, Society and Development, 2020)
Method: to identify the publications about COVID-19 in light of the Brazilian researchers. Method: to make an integrative review of literature through the research of articles published between January and April 2020 with CAPES and SCIELO’s database. Results: the 38 texts selected were analyzed and categorized, and the contents of the texts were well-diversified among economics, health care, and human affairs, with no predominance of a particular subject. This conclusion demonstrates that the subject COVID-19 is an object of study in all areas. Conclusion: the results of this research highlighted that the global economic interdependence is in crisis with all measures of social isolation. However, in the Brazilian scenario, other issues are highlighted, mainly due to the lack of basic infrastructure for the population that is in a vulnerable situation. Thus, the continuous generation of information with studies and research in several areas of knowledge about the course, and the effects of this new epidemic in the country is essential in order to support the decision-making of public agents involved in controlling the epidemic and society in general.